Immune phenotyping of diverse syngeneic murine brain tumors identifies immunologically distinct types - Khalsa, Jasneet Kaur (Nat Commun, 2020)
Immunotherapy has emerged as a promising approach to treat cancer, however, its efficacy in highly malignant brain-tumors, glioblastomas (GBM), is limited. Here, we generate distinct imageable syngeneic mouse GBM-tumor models and utilize RNA-sequencing, CyTOF and correlative immunohistochemistry to assess immune-profiles in these models. We identify immunologically-inert and -active syngeneic-tumor types and show that inert tumors have an immune-suppressive phenotype with numerous exhausted CD8 T cells and resident macrophages; fewer eosinophils and SiglecF+ macrophages. To mimic the clinical-settings of first line of GBM-treatment, we show that tumor-resection invigorates an anti-tumor response via increasing T cells, activated microglia and SiglecF+ macrophages and decreasing resident macrophages. A comparative CyTOF analysis of resected-tumor samples from GBM-patients and mouse GBM-tumors show stark similarities in one of the mouse GBM-tumors tested. These findings guide informed choices for use of GBM models for immunotherapeutic interventions and offer a potential to facilitate immune-therapies in GBM patients.